VALIDASI METODE ANALISIS SENYAWA ETIL p-METOKSISINAMAT DALAM PLASMA DARAH TIKUS PUTIH JANTAN GALUR WISTAR MENGGUNAKAN KROMATOGRAFI CAIR KINERJA TINGGI - Revika Rachmaniar; Natalia Suryanata; Nela Simanjuntak (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Ethyl p-methoxycinnamate (EPMC) isolated from the rhizome of kencur (Kaempferia galanga L) is being developed at STFI. Validation of EPMC analysis in blood plasma using High-Performance Liquid Chromatography (HPLC) needs to be conducted to perform in vivo EPMC analysis. This study aims to validate the EPMC analysis method in blood plasma using HPLC. The HPLC column used is column C18, with methanol : phosphoric acid 70:30 and 80:20 mobile phases, a flow rate of 1.0 mL/min, and a maximum wavelength of 310 nm. The blood plasma used was the blood plasma of white male rats of the Wistar strain. EPMC was added to blood plasma and analyzed using HPLC. Parameter validation used is system suitability test, linearity, accuracy, precision, limit of detection (LOD), and limit of quantification (LOQ). The results showed that the optimum mobile phase for analyzing EPMS in plasma was methanol : phosphoric acid with a ratio of 70:30. Based on the validation, the linear regression was 0.998. In the accuracy test, the average value range for the percent recovery is 98% - 102%. In the precision test, the average value of the RSD percentage was 4.10% - 68.83%. The LOD value is 2.747 g/mL, and the LOQ value is 9.158 g/mL. Based on this research, it can be concluded that EPMC in blood plasma can be analyzed using KKKT with column C18 and mobile phase methanol : phosphoric acid 70:30.